Corporate Social Responsibility: a Case Study in Subsidiaries from Brazil and China - Prates, Caroline Chagas; Pedrozo, Eugenio Avila; Silva, Tania Nunes (Journal of Technology Management & Innovation, 2015)
Corporate Social Responsibility refers to the business’ role in providing Sustainable Development through fair and appropriate relationships with its stakeholders. This study aimed to describe and analyze the CSR evolution in two subsidiaries within the same group, one located in Brazil and other in China. In general, observed similarities in CSR evolution. In both companies, the order in which the dimensions received incentives was the same, first the economic, then the environmental and lastly the social dimension. However, some differences were noted, such as the initial situation of dimensions and the time to consolidate the pillars. In Chinese company, the initial situation about environmental and social dimension was worst. Other point refers to time toward CSR. In Brazilian’ subsidiary, the CSR evolution occurred slower. The last point refers to requirements of second order, given the non-observance of these in both subsidiaries.